Preparation and characterization of poly(vinyl alcohol)/chitosan bio-nanocomposites reinforced with cellulose nanocrystals, cellulose nanocrystals/zinc oxide and cellulose nanocrystals/zinc oxide-silver nanoparticles - Azizy, Sussan (2014)
Polymer nanocomposites are materials composed of polymer matrices and nano-sized fillers with enhanced physical and chemical properties in comparison with the pure polymers or conventional composites. Strong research attempts have been focused on the use of bio-polymers because of increasing environmental concerns of using petroleum base polymers. The present research aims to study the influence of cellulose nanocrystals (CNCs), cellulose nanocrystals/zinc oxide nanoparticles (CNCs/ZnO-NPs) and cellulose nanocrystals/zinc oxide-silver nanoparticles (CNCs/ZnO-Ag-NPs) on the properties of poly(vinyl alcohol)/chitosan (PVA/CTS), an important bio-polymer blend. Cellulose nanocrystal was extracted by acid–catalyzed hydrolysis of cotton cellulose.ZnO-NPs and ZnO-Ag-NPs were prepared in suspension of CNCs as a stabilizer via a co-precipitation method. The samples were characterized using Fourier transform infrared (FTIR), energy dispersive x-ray spectroscopy (EDS), ultraviolet-visible (UVvis), x-ray diffraction (XRD), transmission electron microscope (TEM), field emission scanning electron microscope (FESEM), thermogravimetric analysis (TGA) and antimicrobial tests. According to the XRD and TEM results, polygonal structured ZnO nanocrystallites with a mean size of less than 30 nm were formed. The prepared ZnOAg nanocrystallites were spherical with a mean size diameters in a 12–35 nm range. The bio-nanocomposites were prepared by mixing various percentages of nano-sized fillers and PVA/CTS blends in the ratio of 3:1. The properties of the prepared bionanocomposites were studied by XRD, TEM, TGA, UV-vis, barrier, tensile and antimicrobial tests. The PVA/CTS/CNCs bio-nanocomposites with low percentage of the CNCs (1.0 wt%) exhibits maximum mechanical, thermal, and barrier properties. The PVA/CTS/CNCs/ZnO 5.0 wt% bio-nanocomposite exhibits the maximum tensile,and barrier properties. TGA results show that the maximum thermal decomposition of the PVA/CTS increases by about 34 °C at 1.0 wt%. The UV–visible spectrophotometric study shows that the bio-nanocomposites display an excellent performance of absorbing UV light. The antimicrobial tests reveal a favorable antibacterial effect for those PVA/CTS blend films filled with the high levels of CNCs/ZnO-NPs content. The PVA/CTS/CNCs/ZnO-Ag 5.0 wt% bio-nanocomposite shows the maximum tensile,thermal and barrier properties. The UV–visible measurements showed that the bionanocomposites display prefect absorption in the range of 300-700 nm. The all bionanocomposites show antibacterial power, with the maximum effect in the 7.0 wt% of CNCs/ZnO-Ag-NPs loading.